A systematic review on fast fashion - Osman, Syuhaily; Ying, Wing Loo; Lau, Nur Jasmine Leby (Faculty of Human Ecology, Universiti Putra Malaysia, 2022)
Fast fashion industry is consisted of numerous brands; including but not limited to Uniqlo, H&M, Mango, Shein and Padini. It has established itself as the staple source for consumers to shop for a wide range of apparels for past decades in the apparel industry. In contrary to such prominence in consumers’ daily life and the industry, fast fashion is not commonly researched and often studied as traditional fashion, separate category in the apparel industry. Furthermore, the recent rise of environmental consciousness has brought to the occurrence of contradictory behaviour among fast fashion consumers. This paper aims to provide a comprehensive understanding on fast fashion. Analyses from 23 past studies on various aspects of fast fashion (operation management, consumer science, textile engineering, business administration and fashion design) revealed that it is a business model that practises management strategies that contributed to its success in the apparel industry. Fast fashion’s trendy designs and strategic pricing are the common factors that attract consumers’ purchasing behaviour. However, many studies are found to criticise its business model as being unsustainable. The findings also identified gaps of literature in fast fashion concerning behavioural intention, brand perception and trend adoption, even more so in Malaysian context. The literature has been saturated with qualitative approaches which have produced consistent themes (pricing factor, trendiness, sustainability); thus it is recommended to use quantitative approaches to test the prevalence of these themes.